Transcription activation by the bacteriophage Mu Mor protein: analysis of promoter mutations in Pm identifies a new region required for promoter function. - Artsimovitch, I (1996)
Middle transcription of bacteriophage Mu requires Escherichia coli RNA polymerase holoenzyme and a Mu-encoded protein, Mor. Consistent with these requirements, the middle promoter, Pm, has a recognizable -10 region but lacks a -35 region. Mutagenesis of this promoter (from -70 to +10) was performed using mutagenic oligonucleotide-directed PCR. The resulting fragments were cloned into a promoter-lacZfusion vector and analyzed for promoter activity by assaying beta-galactosidase production. Single point mutations with a Down phenotype were clustered in three regions: the -10 region, the Mor footprint region and the spacer between them. Gel retardation experiments with purified Mor protein and promoter mutants demonstrated that sequences important for Mor binding are located within the Mor footprint region and lead us to propose the existence of a dyad symmetry element involved in Mor binding. In agreement with this prediction, glutaraldehyde crosslinking of Mor in solution generated a species with the size of a dimer. These experiments also identified an unusual group of mutations located in the spacer region adjacent to the Mor footprint. These mutations alter promoter activity without affecting Mor binding. A circular permutation assay revealed that Mor does not introduce a significant bend upon binding to its target sequence.